(untitled) - Mark W. Janis; Mark W. Janis; Richard S. Kay; Anthony W. Bradley (Oxford ; New York, 2008)
The third edition of European Human Rights Law: Text and Materials has been substantially expanded to provide a complete review of the wide range of rights the Convention protects, with new chapters on the right to life, property, discrimination, religious freedom, and education. The book introduces both the process and the substance of this increasingly important area of European law
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms (1950); Human rights --Europe; Human rights --Europe --Cases